2012
DOI: 10.1603/an11111
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Genetic Variation among Spodoptera frugiperda (Lepidoptera: Noctuidae) Sampled from the United States, Puerto Rico, Panama, and Argentina

Abstract: ARSTRACT Spatial genetic variability of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), was studied by collecting samples from 31 locations in the United States, Argentina, Panama, and Puerto Rico, and then using amplified fragment length polymorphism to detect genetic variation. Analysis of molecular variance showed significant genetic variation in fall armyworm among all (28%) sample locations and individuals within (71%) sample locations; genetic variation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
2
20
0
2
Order By: Relevance
“…The highest amount of diversity was found among individuals and the correlation analysis confirmed no genetic isolation by geographic distance between S. frugiperda populations, which is in agreement with Martinelli et al (2007), Clark et al (2007), and Belay et al (2012). This poses the question of what maintains this genetic differentiation: geographical distance, host fidelity, or strain identity, and how they are related.…”
Section: Genetic Variability and Population Structuresupporting
confidence: 64%
See 3 more Smart Citations
“…The highest amount of diversity was found among individuals and the correlation analysis confirmed no genetic isolation by geographic distance between S. frugiperda populations, which is in agreement with Martinelli et al (2007), Clark et al (2007), and Belay et al (2012). This poses the question of what maintains this genetic differentiation: geographical distance, host fidelity, or strain identity, and how they are related.…”
Section: Genetic Variability and Population Structuresupporting
confidence: 64%
“…In South American populations there seem to be some differences, as we recently found no consistent pattern of host association between the two forms and their respective host plants when using two restriction site polymorphisms in COI (Ju arez et al, 2012). Most of the work published using molecular markers has been used to identify both forms and assess their host specificity, but provide little information about the genetic diversity and population structure of S. frugiperda, with a few exceptions (McMichael & Prowell, 1999;Busato et al, 2004;Clark et al, 2007;Belay et al, 2012). In using this combination, about 16% of field-collected samples from Louisiana, Florida (both USA), Puerto Rico, Guadeloupe, and French Guiana (Prowell et al, 2004) were found to be potential hybrids due to discordance for at least one marker (mtDNA, esterase, and AFLP), with both types of hybrids (RC and CR; first letter always referring to the female) equally frequent, mostly in maize habitats.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Portanto, devem-se utilizar marcadores que não requeiram conhecimento prévio sobre o genoma. Entre estes, o "amplified fragment length polymorphism" (AFLP) possibilita caracterizar biótipos e detectar a variabilidade genética de S. frugiperda (Busato et al, 2004;Clark et al, 2007;Martinelli et al, 2007;Belay et al, 2012) Creste et al (2001). A separação dos fragmentos foi realizada em eletroforese por 2 horas, a 60 W.…”
Section: Molecular Diversity Among Populations Of Spodoptera Frugiperunclassified